2022
DOI: 10.1111/jir.12933
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary behaviour and screen time among youths with Down syndrome during the COVID‐19 pandemic

Abstract: Background The COVID‐19‐related restrictions hampered habitual physical activity (PA), particularly affecting the more vulnerable, such as people with Down syndrome (DS). The study aimed to investigate changes in PA, sedentary behaviour (SB) and screen time (ST) of youths with DS, before, during and after the restrictions, also in relation to parental PA levels. Methods A cross‐sectional design with a retrospective assessment of variables for the before and during restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The need for engaging and accessible exercise programming has become even more urgent over the course of the COVID-19 pandemic, as activities that can be especially beneficial for individuals with DSlike time outside and time with peershave been curtailed (Hartley et al 2022), while sedentary behaviours and screen time have increased (Amatori et al 2022). Families who already experienced significant barriers to physical activity before the pandemic, like lower-income and lower-resource families, and the families of children with disabilities, now face additional restrictions accessing safe exercise facilities, equipment, and organised fitness activities (Perez et al 2021;Theis et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The need for engaging and accessible exercise programming has become even more urgent over the course of the COVID-19 pandemic, as activities that can be especially beneficial for individuals with DSlike time outside and time with peershave been curtailed (Hartley et al 2022), while sedentary behaviours and screen time have increased (Amatori et al 2022). Families who already experienced significant barriers to physical activity before the pandemic, like lower-income and lower-resource families, and the families of children with disabilities, now face additional restrictions accessing safe exercise facilities, equipment, and organised fitness activities (Perez et al 2021;Theis et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Families who already experienced significant barriers to physical activity before the pandemic, like lower-income and lower-resource families, and the families of children with disabilities, now face additional restrictions accessing safe exercise facilities, equipment, and organised fitness activities (Perez et al 2021;Theis et al 2021). Physical activity levels have subsequently decreased for the majority of children and young adults with disabilities (Amatori et al 2022;Theis et al 2021), demonstrating that better at-home exercise options will continue to be essential moving forward.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional obstacle to increasing physical activity among PWDS is the COVID-19 epidemic that has been present for over 2 years. Amatori et al showed a negative impact of COVID-19: decreased physical activity and increased sedentary behaviors [ 91 ]. It is worth remembering that the patterns of proper nutrition should function throughout a household.…”
Section: Down Syndromementioning
confidence: 99%